Minecraft Woodsword Chronicles: Night of the Bats! - Book 2 - Eliopulos, Nick; Flowers, Luke (New York : Random House, 2019)
"The adventures continue in the Woodsword Chronicles as five young Minecraft players find themselves transported inside the game they love--and now bats have invaded their school! Are creatures from the game leaking into their world? Needing to learn more, the players agree to leave their Minecraft castle and travel farther into the world theyre visiting"--
Keywords: Minecraft (Game) -- Juvenile fiction; Minecraft (Game) -- Fiction